Tony Manero [videorecording (DVD)] - Larraín, Pablo; Larraín, Pablo; Noguera, Amparo, 1965-; Morales, Héctor; Poblete, Elsa (Lorber Films, 2010)
Raúl Peralta, a middle-aged criminal in 1970's Chile, is obsessed with the idea of impersonating Tony Manero, John Travolta's character in Saturday Night Fever. Every Saturday evening, he unleashes his passion for the film's music by imitating his idol and leading a small group of dancers as they perform at a bar in the outskirts of the city. His dream of being recognized as a successful showbiz star is about to become a reality when a Tony Manero impersonating contest is announced on national television. However, his obsession to reproduce his idol's likeness and perfect his act drives him to commit a series of violent crimes and thefts, leading to shocking violence and murder.